THE ELASMOBRANCH NURSERY AREA OF JAKARTA BAY - Fahmi, - (Marine Research in Indonesia, 2012)
A study on the correlation between water, sediment qualities and the diversity of elasmobranchs in Jakarta Bayhas been conducted by the Research Center for Oceanography from the beginning of 2012. This paper presents apart of the study focusing on elasmobranch diversity and its size composition. Elasmobranchs in the coastal area ofJakarta Bay were collected using bottom gillnet every month to find out the species diversity and its size composition.The 162 collected individuals from Jakarta Bay were classified into eight species of rays and one whaler shark.Himantura gerrardi, H. uarnacoides, H. walga and Neotrygon kuhlii were the most common species found in thisarea. Interestingly, most specimens found in the area were immature and new born animals. This finding indicatesthat the coastal area of Jakarta Bay is one of nursery areas of most elasmobranchs living in adjacent waters althoughthe bay has been heavily polluted.